Relationship between changes in the translational apparatus and actinomycin production in Streptomyces antibioticus. - Jones, G H (1977)
As previously reported (G. H. Jones, 1975), transfer ribonucleic acids (tRNA's) and ribosomes from actinomycin-producing cultures of Streptomyces antibioticus show a decreased ability to function in aminoacylation and translation as compared with the corresponding components from younger cells. Further, specific changes in the isoacceptor patterns are revealed when tRNA's from actinomycin-producing cells are compared with those of younger cells by reverse- phase column chromatography. A specific glycyl-tRNA species is eliminated from the reverse-phase profile of tRNA's from actinomycin-producing S. antibioticus cells as compared with younger cells. Changes in isoacceptor patterns were also observed for the amino acids methionine, valine, phenylalanine, and leucine. Actinomycin synthesis was inhibited by growing S. antibioticus cells in the presence of alpha-methyl-DL-tryptophan. Inhibition of actinomycin synthesis reversed the changes in tRNA observed in normally grown control cultures, although it had no demonstrable effect on the growth of the cells. Thus, tRNA from 48-h-old, alpha-methyl-tryptophan-grown cells had amino acid acceptor activity that was equal to or greater than that of tRNA from 12-h-old, normally grown cells. Similarly, the reverse-phase chromatographic pattern for glycyl-tRNA's from 48-h-old, alpha-methyl-tryptophan-grown cells was identical to that of the glycyl-tRNA's from 12-h-old, normally grown cells. In contrast, the ability of ribosomes from 48-h-old, alpha-methyl-tryptophan-grown cells to function in polypeptide synthesis in vitro was essentially identical to that of 48-h-old, normally grown cells. Ribosomes from 12-h-old, normally grown cells were severalfold more active in in vitro polypeptide synthesis.